Management of pediatric obesity as a pathway towards kidney transplantation - Altemose, K. E.; Nailescu, C. (Frontiers in Pediatrics, 2024)
Obesity is an increasing problem in pediatrics, leading to cardiovascular, metabolic and psychosocial complications. Additionally, for patients with chronic kidney disease (CKD), obesity can lead to CKD progression towards end-stage renal disease (ESRD) needing renal-replacement therapy (RRT). It is well-established that the optimal type of RRT for children with ESRD is kidney transplantation, as it provides significantly better life expectancy and quality of life. Unfortunately, pediatric patients with CKD/ESRD and obesity face barriers getting to kidney transplantation and often remain on dialysis for a long time, which negatively impacts their life expectancy and quality of life. One barrier to kidney transplant is that Body Mass Index (BMI) is still considered by most transplant centers as the main criterion for obesity assessment, although more recent evidence suggests that BMI is not the best measure of adiposity. Clearcut evidence is lacking that obesity has a long-term negative impact upon the graft. Another barrier to transplant can be bias on the part of referring providers that can deter or delay referral to an obesity treatment program. Our article describes the barriers that pediatric obese patients with CKD and ESRD face in their way towards kidney transplantation. In addition, our article encourages pediatric nephrologists to early refer their patients with CKD and ESRD who suffer from obesity to a specialized obesity treatment program and/or bariatric surgery. Our article also describes the treatment options for pediatric patients with CKD and ESRD who suffer from obesity in order to make them eligible for a kidney transplant.